Trinidad and Tobago : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics, Banking Supervision, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses Trinidad and Tobago's (TTO) Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Banking Supervision, and Payment Systems. TTO's financial system is relatively large and structurally complex, demonstrating both sophistication and oligopolistic concentration. Although it does not appear to be vulnerable to immediate-term macroeconomic shocks, its risk profile has evolved. Stress tests and the assessment of compliance with Basel Core Principles indicate that the banking system is well capitalized and profitable, but is vulnerable to the potential macroeconomic impact of a sharp fall in energy prices.